Mutations in LOXHD1 Gene Cause Various Types and Severities of Hearing Loss. (May 2015) - Mori, Kentaro; Moteki, Hideaki; Kobayashi, Yumiko; Azaiez, Hela; Booth, Kevin T.; Nishio, Shin-ya; Sato, Hiroaki; Smith, Richard J. H.; Usami, Shin-ichi
Objective: We present 2 families that were identified with novel mutations in LOXHD1 as a cause of nonprogressive hearing loss. Methods: One thousand three hundred fourteen (1314) Japanese subjects with sensorineural hearing loss from unrelated families were enrolled in the study. Targeted genomic enrichment and massively parallel sequencing of all known nonsyndromic hearing loss genes were performed to identify the genetic cause of hearing loss. Results: Two patients in 1 family affected with homozygous mutation c.879+1G>A in LOXHD1 showed profound congenital hearing loss, whereas 2 patients in another family with compound heterozygous mutations, c.5869G>T (p.E1957X) and c.4480C>T (p.R1494X), showed moderate to severe hearing loss. Conclusion: Mutations in LOXHD1 are extremely rare, and these cases are the first identified in a Japanese population. The genotype-phenotype correlation in LOXHD1 is still unclear. The differences in phenotypes in each patient might be the result of the nature of the mutations or the location on the gene, or be influenced by a genetic modifier.